Onion harvester with topping unitA complete harvesting machine for onion - Naik, Mude Arjun; Pateriya, R N; Ramulu, Ch. (Indian Farming, 2024)
Onion harvesting is one of the main important agriculture operation. It involves topping of onion leaves up to its neck, digging, soil separation, windrowing and collection. The manual method of onion harvesting involves pulling out plants from the soil or digging with locally available khurpa; then, removal of onion leaves requires a high labour force of nearly about 200-280 man-h per ha, costing about `4200, and it is a tedious job resulting in fatigue and drudgery to workers. Further, the time available for harvesting onion during peak season is limited, causing high labour demand and cost. In addition, the late and early harvesting of onion also effect the storage life. Thus, harvesting onion within a specified time suitable for market needs is the most important factor in onion harvesting. Hence, an onion digger with a topping unit is a machine that harvests onion suitable to market needs in a single pass with a saving of cost to the tune of 57.09% over the conventional harvesting method.